Interictal regional slow activity in temporal lobe epilepsy correlates with lateral temporal hypometabolism as imaged with18FDG PET: neurophysiological and metabolic implications. Issue 2 (1st August 1998) - Koutroumanidis, Michael; Binnie, Colin D; Elwes, Robert D C; Polkey, Charles E; Seed, Paul; Alarcon, Gonzalo; Cox, Tim; Barrington, Sally; Marsden, Paul; Maisey, Michael N; Panayiotopoulos, Chrysostomos P
Abstract : OBJECTIVES: The phenomenon of interictal regional slow activity (IRSA) in temporal lobe epilepsy and its relation with cerebral glucose metabolism, clinical data, MRI, and histopathological findings was studied. METHODS: Interictal 18 F-fluorodeoxyglucose positron emission tomography (FDG PET) was performed under continuous scalp EEG monitoring in 28 patients with temporal lobe epilepsy not associated with intracranial foreign tissue lesions, all of whom subsequently underwent resective surgery. Regions of interest (ROIs) were drawn according to a standard template. IRSA was considered lateralised when showing a 4:1 or greater ratio of predominance on one side. RESULTS: Sixteen patients (57%) had lateralised IRSA which was always ipsilateral to the resection and of maximal amplitude over the temporal areas. Its presence was significantly related to the presence of hypometabolism in the lateral temporal neocortex (p=0.0009). Logistic regression of the asymmetry indices for all measured cerebral regions confirmed a strong association between IRSA and decreased metabolism of the posterior lateral temporal neocortex only (p=0.009). No significant relation could be shown between slow activity and age at onset, duration of the epilepsy, seizure frequency, and MRI evidence for hippocampal atrophy. Furthermore, IRSA was not specifically related to mesial temporal sclerosis or any other pathology. CONCLUSIONS: Interictal regional slowing in patients with temporal lobe epilepsy not associated with a mass lesion is topographically related to the epileptogenic area and therefore has a reliable lateralising, and possibly localising, value. Its presence is irrelevant to the severity or chronicity of the epilepsy as well as to lateral deactivation secondary to neuronal loss in the mesial temporal structures. Although slow EEG activity is generally considered as a non-specific sign of functional disturbance, interictal regional slowing in temporal lobe epilepsy should be conceptualised as a distinct electrographic phenomenon which is directly related to the epileptogenic abnormality. The strong correlation between interictal regional slowing and lateral temporal hypometabolism suggests in turn that the second may delineate a field of reduced neuronal inhibition which can receive interictal and ictal propagation.